2018
DOI: 10.1002/jcp.26479
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted link between inflammation and human diseases

Abstract: Increasing reports on epidemiological, diagnostic, and clinical studies suggest that dysfunction of the inflammatory reaction results in chronic illnesses such as cancer, arthritis, arteriosclerosis, neurological disorders, liver diseases, and renal disorders. Chronic inflammation might progress if injurious agent persists; however, more typically than not, the response is chronic from the start. Distinct to most changes in acute inflammation, chronic inflammation is characterized by the infiltration of damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 137 publications
1
83
0
Order By: Relevance
“…Inflammatory reaction results in chronic illnesses, including cancer (Rajendran et al, ). Inflammation is a hallmark of cancer and is a known driver of cancer development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory reaction results in chronic illnesses, including cancer (Rajendran et al, ). Inflammation is a hallmark of cancer and is a known driver of cancer development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress occurs when reactive oxygen species (ROS) overload the body's defenses or when these defenses lose their capacity to react, leading to damage of essential cell components [11]. Experimental, clinical, and epidemiological studies have revealed that this status is involved in the development of NCDs such as arteriosclerosis, obesity, type 2 diabetes, inflammatory bowel disease, arthritis, neurological, liver, and renal disorders, and cancer [12]. Hypertension, defined as high blood pressure, is currently considered one of the major preventable risk factors linked to cardiovascular diseases [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are accumulating evidences that highlight the role of RPs in regulation of critical cellular processes independent of their canonical functions in ribosome biogenesis and protein synthesis [14,33,34]. Role of inflammation is now widely recognized with progression of a number of diseases in humans, for example atherosclerosis, cancer and rheumatoid arthritis [35]. Only a few reports are available that demonstrate the association of individual RPs in inflammation.…”
Section: Discussionmentioning
confidence: 99%